Effect of vitamin C supplementation on lipid profiling and oxidative stress in type 2 diabetic patients: A randomised placebo-controlled trial study - Ali, Faisal; Othman, Gamil (Nutrition Society of Malaysia, 2020)
Vitamin C is one of the most important antioxidants that inhibits lipid peroxidation and improves endothelial function. Diabetic dyslipidemia is the cause of oxidative stress-induced vascular damage along with the simultaneous decline of antioxidant defense system leading to cellular damage, increased lipid peroxidation and subsequent development of severe complications in type 2 diabetes mellitus (DM). Antioxidant vitamin C has been reported to reduce oxidative stress by arresting free radical damage and thereby improves lipid levels in type 2 DM patients. The present study was aimed to investigate the impact of oral vitamin C supplementation with metformin on lipids and oxidative stress biomarkers in patients suffering from type 2 DM. Sixty patients with type 2 DM were divided randomly into placebo and vitamin C group. The patients were randomly divided into two groups: Group I (study group, n=30) received intravenous 250 mg of vitamin C supplementation and Group II (control, n=30) received placebo (intravenous saline) twice daily for 12 weeks. The study will be approved by the Ethics Committee of Faculty of Medicine, UST University, and all patients will be gave written informed consent to participate in this study. This prospective study will be performed in the Internal Medicine Unit at the UST University Hospital, during the period from January 2021 to August 2021. Sixty diabetic patients on anti-diabetic therapy will be enrolled in this study. The treatment, diet and physical activity of the patients remained unchanged during the course of study. All patients will be subjected to full history taking, thorough clinical examination and laboratory investigations. Laboratory investigations include serum MDA, oxidized low-density lipoprotein, CRP, prostaglandins, plasma ascorbic acid, serum triglyceride, total serum cholesterol, high-density lipoprotein (HDL), and LDL.